Preterm and term birth in twin pregnancies during a seven-year period: a call for obstetricians to declare about amnionicity and chorionicity - Anis Cerovac; Gordana Grgić; Dženana Softić; Dženita Ljuca; Sergije Marković; Amer Mandžić (Medicinski glasnik, 2020)
Aim: To compare maternal, foetal and neonatal characteristics, and perinatal outcome of preterm and term deliveries in twins pregnancies in order to improve perinatal care in Bosnia and Herzegovina. Methods: This retrospective cohort study included pregnant women with twin pregnancy who delivered during the period between 1 January 2012 and 31 December 2018 at the Clinic for Gynaecology and Obstetrics, University Clinical Centre Tuzla. Results: During the seven-year period 26 734 deliveries were recorded, out of which 362 (1.35 %) were twin pregnancies, 226 (62.4%) preterm and 136 (37.5%) term ones. In the preterm group 38 (16.8%) pregnancies were assisted medical reproduction, and 16 (11.7%) of those were in the term group. The average birth weight was significantly higher for the first twin in both groups (p<0.00001). Incipient intrauterine foetal asphyxia was more frequent in the preterm group (p<0.05). The most common indication for Caesarean section was abnormalities of foetal presentation and lie, 176 (68.2%) for the overall sample. Conclusion: Cornerstone of twin pregnancy antenatal care is to get correct data about amnionicity and chorionicity. Since majority of prenatal data did not have this information we call all obstetricians to declare about amnionicity and chorionicity in twin pregnancies during the first trimester ultrasound examination.
Keywords: foetal membranes; multiple pregnancy; premature labour; prenatal care